2019
DOI: 10.1097/phh.0000000000001034
|View full text |Cite
|
Sign up to set email alerts
|

Are Nonprofit Hospitals Addressing the Most Critical Community Health Needs That They Identify in Their Community Health Needs Assessments?

Abstract: Context: Virtually all nonprofit hospitals are in compliance with the Affordable Care Act's new Community Health Needs Assessments requirements. Objective: To assess what needs have emerged in the Community Health Needs Assessments hospitals complete nationally, the degree to which identified needs reflect the most pressing community health issues, and the extent to which hospitals address identified needs. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 17 publications
2
53
0
Order By: Relevance
“…These efforts have also been bolstered by new community benefit requirements included in the Affordable Care Act (ACA). The ACA requires nonprofit hospitals, nearly two-thirds of hospitals in the US, to regularly assess and report on pressing community health needs ( Franz, Cronin, & Singh, 2019 ; Pennel, McLeroy, Burdine, Matarrita-Cascante, & Wang, 2016 ). More specifically, nonprofit hospitals must complete a Community Health Needs Assessment (CHNA) every three years and propose specific interventions to improve community health in a corresponding implementation strategy in exchange for tax exemption ( James, 2016 ).…”
Section: Theorymentioning
confidence: 99%
“…These efforts have also been bolstered by new community benefit requirements included in the Affordable Care Act (ACA). The ACA requires nonprofit hospitals, nearly two-thirds of hospitals in the US, to regularly assess and report on pressing community health needs ( Franz, Cronin, & Singh, 2019 ; Pennel, McLeroy, Burdine, Matarrita-Cascante, & Wang, 2016 ). More specifically, nonprofit hospitals must complete a Community Health Needs Assessment (CHNA) every three years and propose specific interventions to improve community health in a corresponding implementation strategy in exchange for tax exemption ( James, 2016 ).…”
Section: Theorymentioning
confidence: 99%
“…We interpret these findings to mean that many hospitals, and children's hospitals in particular, may be including health needs that are broader than the immediate county or reflect other priorities, such as needs that are considered highly relevant by local residents or by the hospital. One previous study found a high level of overlap between county health indicators and the prioritization of needs in CHNAs among general hospitals (32). With children's hospitals included, our findings may reflect a broader focus on regional, rather than county-level, health needs.…”
Section: Discussionmentioning
confidence: 56%
“…Our findings provide important insight into the decisions that hospitals make to include health needs as top priorities in their CHNAs. A past study found that hospitals that ranked needs at the top of their list of prioritized needs are more likely to have accompanying strategies to address these needs in their implementation strategies (32). As such, hospital decisions to prioritize a need in their CHNA are likely related to the presence of actionable strategies in the corresponding implementation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that there are both substantial overlaps within communities but also strengthen the idea that needs assessment should be done at the local level and not just across the system to identify needs that might exist within smaller pockets of a system's service area and might be best served by an individual hospital site rather than leveraging system resources. A combination of local level data collection [especially considering the need to link local population health data and rankings to the needs selected by individual hospitals (18)] and CHNA reports and a system-wide reporting and implementation planning mechanism would be a strong combination for healthcare systems looking to have an impact on large-scale population health. These findings reiterate findings in the literature speaking to the importance of regional planning for community benefit (16).…”
Section: Discussionmentioning
confidence: 99%